Immunoglobulin Based Therapeutic Approach for Parvo Virus Infection in Dog: A Case Report - Naba Jyoti Deka; Dhruba Jyoti Kalita; Prasanta Chabukdhara; Derhasar Brahma; Chinmoy Dutta; Biraj Bania (Archives of Current Research International, 2024)
Canine parvo viral infection is a highly contagious disease in dog with high mortality rate in untreated cases. This study represents a case report of an unvaccinated 4 months old German shepherd puppy presented with a history of profuse foetid diarrhoea, vomition, inappetence and depression for 2 days. Physical examination of the dog revealed sub normal temperature (99.5°F), abdominal pain, bloat, severe dehydration and debility. Haematology showed low RBC count, low Hb level, low Hct value, lower MCV and mild lymphopenia. The dog was diagnosed as canine parvoviral infection based on the result of rapid antigen test and the characteristic clinical findings. The treatment included fluid replacement therapy, antimicrobial drug, antiemetic, haemostatic agent along with immunoglobulins. An instant onset of passive immunity is developed upon IV administration of immunoglobulins. The pup showed good response from 3rd day of the treatment and finally recovered successfully. Thus, administration of specific immunoglobins along with standard treatment regimen in canine parvo virus infection can be effective in reducing mortality in dogs.